Amplification and Transposition in English Commands and Its Translations into Indonesian with Reference to the Novel Entitled Harry Potter and The Order of Phoenix - Putu Diah Darmayanti (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2020)
Every human has their own characteristics of languages and in order to understand one language to another languages, then, translation was essential and fully needed. In order to avoid the awkward translation, therefore the translator must use a technique in translating the texts. The research aimed at analyzing the equivalence between the source language and its translations based on the translation techniques applied by translator. This research focused on the amplification and transposition techniques could be seen on the imperative sentences especially command. The research was conducted by applying qualitative method. The research was conducted by applying library research and observation methods. The collected data were analyzed using descriptive qualitative method. The study applied two methods to present the analysis of data as follows informal and formal method. Target of research did not involve participants however, this research focused on analyzing data was English commands and its translation into Indonesian by using amplification and transposition found in the novel. The result of research showed amplification and transposition were dominant used in translating the English commands (SL) into Indonesian (TL). The translator applied amplification and transposition to find equivalences when transferring the meaning from the source language (SL) into target language (TL). Therefore, the overlapping translation could be minimized. Amplification had a role especially the addition of information. The phenomena occurred when the detail information did not contain in the SL and the translator must be sensitive by putting the necessary information in TL. Transposition created three parts of shift: structure, unit, and class of shift.